2021
DOI: 10.3390/su13147742
|View full text |Cite
|
Sign up to set email alerts
|

Do Tourism Activities and Urbanization Drive Material Consumption in the OECD Countries? A Quantile Regression Approach

Abstract: The United Nations Sustainable Development Goals (UNSDGs) elaborately encompass a global goal for sustainable consumption and production (Goal 12: SDGs), thus providing potential drivers and/or pathways to attaining sustainable consumption. In view of this global goal, this study examined the role of real income per capita, urbanization and especially inbound tourism in domestic material consumption for the panel of OECD countries. The study is conducted for the period of 1995 to 2016 by employing the panel qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The study unveiled a U-shaped relationship between the variables and that urbanization Granger causes CO 2 emissions. Lasisi et al (2021) investigated the role of real income per capita, urbanization and tourism on domestic material consumption in OECD countries from 1995 to 2016 employing the panel quantile technique. The results revealed an inverted U-shaped relationship between outbound tourism and domestic material consumption across the quantiles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study unveiled a U-shaped relationship between the variables and that urbanization Granger causes CO 2 emissions. Lasisi et al (2021) investigated the role of real income per capita, urbanization and tourism on domestic material consumption in OECD countries from 1995 to 2016 employing the panel quantile technique. The results revealed an inverted U-shaped relationship between outbound tourism and domestic material consumption across the quantiles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Control variables: To capture the character of the city where a CNSA was located, several control variables, such as economic development ( x 1 , measured by per capita gross domestic product), consumption ( x 2 , measured by per capita retail sales of consumer goods), industrial structure upgrading ( x 3 , measured by the shares of tertiary industry in the local gross domestic product), infrastructure ( x 4 , measured by per capita urban road area), green rate ( x 5 , measured by the green coverage rate of built-up area), the air pollution of sulfur dioxide ( x 6 , measured by per capita emission of sulfur dioxide), the air pollution of dust ( x 7 , measured by per capita emission of dust), and the liquid pollution of wastewater ( x 8 , measured by per capita emission of wastewater), were employed by referring to the studies in [ 4 , 7 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, except for CNSAs and time-limited rectification, other influencing factors, including government cooperation and environmental regulation, may have remarkable effects on tourism economic development [ 8 , 10 ]. In addition, to achieve an optimal balance of economic development and conservation of environmental resources, how the tourism economy affects the local ecological environment, energy consumption, and urbanization may be potential investigation directions, which also has great theoretical and practical significance for similar emerging countries [ 1 , 4 ].…”
Section: Conclusion Policy Implications and Research Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, preference comes under the legitimacy value of the instrument selection criteria. Although a sustainable environmental condition is a common interest (Lasisi et al, 2021;Malik et al, 2019), people prefer to accept different policy instruments. For example, (Rissman et al, 2017) found high support for regulatory and market-based water quality policies and relatively low support for policies that rely on voluntary action.…”
Section: Instrument Choice Theorymentioning
confidence: 99%